Anti-Inflammatory Effects of Moringa Oleifera Lam Leaf Extract in Lipopolysaccharide-Activated Microglia - Thampithak, Anusorn; Karachot, Busarat; Jantaratnotai, Nattinee; Tuchinda, Patoomratana; Sanvarinda, Pimtip (Trends in Sciences, 2024)
Moringa oleifera Lam has been used as a medicinal plant in many Asian countries including Thailand. The plant has a variety of pharmacological effects such as antioxidant, anti-inflammation, hypolipidemic, anti-infection, anticancer, and antidiabetic. The leaves and young pods, which contain various nutritional compounds including proteins, fatty acids, and vitamins, are widely consumed. In this study, we investigated the effects of hexane, ethyl acetate, methanol and ethanol crude extracts of M. oleifera Lam leaves on the viability of microglial cells and on the lipopolysaccharide-induced microglial activation. which is widely used as a model for neuroinflammation. Our findings suggested that all of the crude extracts at concentrations ranging from 10–9 to 10–5 g/mL did not significantly affect the viability of microglial cells and exhibited similar effects. Subsequently, we focused on ethanol extract for investigation of the molecular mechanism involving neuroinflammation. We found that the ethanol extract of M. oleifera Lam leaves at the concentrations of 10–9 to 10–5 g/mL significantly reduced inducible nitric oxide synthase (iNOS) protein expression and nitric oxide (NO) production, accompanied by the reduction of phospho-NF-κB and phospho-IκBα expressions. The results suggested that the ethanol extract of M. oleifera Lam leaves reduced NO production through reduction of iNOS protein expression following the inhibition of NF-κB/IκBα signaling pathways. Our study underscored the therapeutic potential of M. oleifera Lam leaves extract in neurodegenerative diseases associated with neuroinflammation. HIGHLIGHTS The ethanol extract of M. oleifera Lam leaves dose-dependently reduced NO production in LPS-activated microglia The reduction in NO production correlated with the reduction in iNOS protein expression The extract inhibited the expression of NF-kB/I-kBα protein expression in a dose-dependent manner The ethanol extract of oleifera Lam leaves exhibited anti-inflammatory effect via the inhibition of NF-kB/I-kBα signaling pathway GRAPHICAL ABSTRACT